Militarizing Men: Gender, Conscription, and War in Post-Soviet Russia - BG Miller (Slovo, 2012)
Miller, BG (2012) Militarizing Men: Gender, Conscription, and War in Post-Soviet Russia. By MAYA EICHLER. Pp. 239. Stanford: Stanford University Press. 2012. $80. Cloth. ISBN: 9780804776196. $24.95. Paperback. ISBN: 9780804776202. [Review]. Slovo , 24 (2). Click here to read the review.